The Status Epilepticus in Adults: Results from a Tertiary Care Teaching Hospital in Karachi, Pakistan (Bangladesh Journal of Medical Science, 2023)
Background: Status epilepticus is one of the common neurological emergencies associated healthcare costs, morbidity and mortality worldwide. The prevalence is more in extreme ages, in adults as well as in children. However, it can occur at any age.Aim: The aim of this study was to determine the possible causes and outcomes of status epilepticus in adults.Method: Across-sectional study was conducted in the department of Neurology, at Jinnah Postgraduate Medical College, Karachi during January 2015 to March 2016. All patients of either gender between 18-60 years of age diagnosed for status epilepticus, presented within 24 hours of their first episode of status epilepticus were included in the study. Patients were examined for the assessment of nature, type and presence or absence of precipitating factors (noncompliance, systemic infection, head trauma and central nervous system infections). Data was entered and analyzed by using SPSS version 19.0.Results: A total number of 241 patients were recruited. We observed that the patients with no previous history of epilepsy 41(17%) had central nervous system infections, followed by head trauma 27(11%), systemic infections 22(9%) and 3(1.2%) were stroke. In patients who were known case of epilepsy 70(29.0%) patients were found non-compliant to Anti-Epiliptic Drug while 30(12.4%) patients were found to have hyponatremia. In 48(19.9%) patients no obvious cause was found.Conclusion: Status epilepticus is not common in our setup and predominant type is convulsive status and none of our patients have non convulsive status. Most common precipitating factor was infections followed by trauma. Further studies of bigger dimension are needed to substantiate these findings.Bangladesh Journal of Medical Science Vol. 22 No. 01 January’23 Page : 128-134